English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

If y(x-1)=z then x=
can someone explain this to me so it makes sense (not just the answer)

2006-11-16 11:00:12 · 5 answers · asked by Belinda M 1 in Science & Mathematics Mathematics

5 answers

y(x-1) = z
Distribute the y
yx - y = z
Add y to each side
yx = z + y
Divide both sides by y
x = (z+y)/y

2006-11-16 11:03:55 · answer #1 · answered by MsMath 7 · 4 3

hi x=(z/y)+1

2006-11-16 19:09:39 · answer #2 · answered by mane 5 · 2 0

y(x-1)=z <--- Distributive Property

yx-y=z

yx-y+y=z+y <--- Add y to each side

(yx)/y = (z+y)/y <--- Divide both sides by y

x= (z+y)/y <---- Simplify



x= (z/y) +1

2006-11-16 20:41:13 · answer #3 · answered by Jasmine 5 · 2 0

Distrubute and solve for x:

(x(y) - 1(y) = z
xy - y = z

Now we want to isolate x:

xy = z + y
x = (z + y)/y

Voila! Hope this helps :)

2006-11-16 19:04:14 · answer #4 · answered by disposable_hero_too 6 · 3 0

yx-y=z
yx=z+y
x=(z+y)/y

2006-11-16 19:03:57 · answer #5 · answered by      7 · 4 0

fedest.com, questions and answers